Pengaruh Giro Wajib Minimum Dan Loan To Deposit Ratio Terhadap Return On Asset - Shadam Azzahra Ross; Nusa Muktiadji; Heri Sastra (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine the effect of the Giro Wajib Minimum and Loan to Deposit Ratio on Return On Assets in banking companies included in Book IV for the period 2014-2019. The method was used a descriptive qualitative method with data obtained secondary from the financial statements of each bank. Data were analyzed using descriptive qualitative analysis methods with multiple linear regression analysis, determination analysis, simultaneous significance test (F test) and partial significance test (t test). The results of this study indicate that: 1) Statutory Reserves have no effect on ROA, 2) Loan to Deposit Ratio has a negative and significant effect on ROA 3) The Statutory Reserves and Loan to Deposit Ratio have a significant effect on Return On Assets. Keywords: Statutory Reserves, Loan to Deposit Ratio, dan Return On Assets